If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8n + -9 = n + 285 Reorder the terms: -9 + 8n = n + 285 Reorder the terms: -9 + 8n = 285 + n Solving -9 + 8n = 285 + n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-1n' to each side of the equation. -9 + 8n + -1n = 285 + n + -1n Combine like terms: 8n + -1n = 7n -9 + 7n = 285 + n + -1n Combine like terms: n + -1n = 0 -9 + 7n = 285 + 0 -9 + 7n = 285 Add '9' to each side of the equation. -9 + 9 + 7n = 285 + 9 Combine like terms: -9 + 9 = 0 0 + 7n = 285 + 9 7n = 285 + 9 Combine like terms: 285 + 9 = 294 7n = 294 Divide each side by '7'. n = 42 Simplifying n = 42
| (-9n+4)-(-2n+(-5))= | | 2abs(x-15)+abs(15-x)=27 | | 25/5(2+3)=1 | | (5n+4)-(6n+(-2))= | | -4b+7=b+212 | | 8x+3(3x)=68 | | -9z+12=10z+12+4z | | 12(14z-11)= | | (2x+4)+(2x+2)=4(x-1)+8 | | Y-1=-x-3 | | =3x+7 | | -5-2x=-(-x-1) | | -2x+6-2x=-4x+6 | | 4t+3t-t+17=8+-3 | | x^2+4x+4=121 | | 7t(t-16)=0 | | 4+13g=17+4g+10g | | (8n+8)-(9n+3)= | | (3-w)(2w-1)=0 | | (n+7)-(6n+(-2))= | | a+238=-5a+4 | | 4x-(6+7)=7x-23 | | xy=a-b | | 5.8(3+3x)-3.4=14 | | (-10.3)+(-0.08)x=-4.7 | | (2n+2)-(-3n+3)= | | (1-3x)-(8-10x)= | | 19+2g=-17g-15+2g | | 4+a=15 | | 3000-20%= | | (-3n+(-6))-(-5n+2)= | | 5(3)=10y+20 |